Analisis Bukti Digital Direct Message Pada Twitter Menggunakan Metode National Institute Of Justice (NIJ) - Yudharta Arif; Erick Irawadi Alwi; Muhammad Arfah Asis (Faculty of Computer Science, University of Jember, 2023)
Twitter is a social media application that can be used on desktop, web and smartphone systems. The large number of Twitter users makes Twitter inseparable from cyber crimes, such as pornography, online gambling, hate speech and other crimes. The purpose of this study is to conduct a forensic investigation on the Twitter Direct Message (DM) application using the NIJ method and determine the success rate of forensic tools in finding deleted data. This study uses the National Institute of Justice (NIJ) method with the stages of identification, collection, examination, analysis, and reporting assisted by forensic tools to obtain digital traces that can be used as evidence. The results obtained from this study were the discovery of evidence of deleted chats and images on Twitter DMs with a success rate of forensic tools (Magnet AXIOM and MOBILEedit) in finding these evidences of 66.66%.